The Druze between Palestine and Israel 1947–49 - Parsons, L. author. aut Link
XVII, 180 p.
Keywords: The Palestinian Druze are the only Israeli Arabs who are conscripted into the Israeli army today. Based on Israeli military and political documents, this book looks at the origins of the Druze's unique status in Israeli society by telling the story of the military and political alliance that emerged between the Druze and the Jewish army in the 1948 war.